Associations between Absolute and Relative Lower Body Strength to Measures of Power and Change of Direction Speed in Division II Female Volleyball Players - Whitney Tramel; Robert G. Lockie; Keston G. Lindsay; J. Jay Dawes (MDPI AG, 2019)
Volleyball is a sport comprised of multiple explosive efforts and multidirectional change of direction speed (CODS) actions. Since strength underpins both of these abilities, it is important to explore the relationship between these variables in order to develop strength and conditioning programs to optimize performance. The purpose of this study is to determine if a relationship exists between absolute and relative strength and measures of power and CODS in collegiate volleyball players. Archived testing data from ten (n = 10, age: 19.1 ± 1.2 yrs, Ht: 173.1 ± 6.64 cm, Wt: 67 ± 7.04 kg) female DII collegiate volleyball players were analyzed. These data included: block vertical jump (Block VJ), approach vertical jump (Approach VJ), a repeat jump test (i.e., four consecutive VJs), modified T-test, 5-0-5 agility test, a single leg triple hop test, and a 1-3RM deadlift. Significant large correlations were observed between relative strength and the repeat jump test, modified T-test, and 5-0-5 agility test. Significant correlations were also observed between absolute strength and the modified T-test. These results indicate that strength and conditioning professionals should emphasize the development of both absolute and relative lower-body strength to improve measures of power and agility in collegiate volleyball players.